Leishmaniasis Diagnosis via Metagenomic Next-Generation Sequencing - Chen, Hongbin; Fan, Chunhong; Gao, Hua; Yin, Yuyao; Wang, Xiaojuan; Zhang, Yawei; Wang, Hui (Frontiers in Cellular and Infection Microbiology, 2020)
Leishmaniasis is a vector-borne disease caused by Leishmania. Although the incidence of leishmaniasis in China is currently low, it has not been completely eradicated. In 2019, we confirmed a diagnosis of visceral leishmaniasis in three patients by combined bone marrow microscopic examination and metagenomic next-generation sequencing (mNGS). Bone marrow mNGS results from three patients indicated that 99.9%, 99.6%, and 30.3% of non-human reads matched the Leishmania genome, respectively, and plasma mNGS results from one of the patients revealed that 46.2% of non-human reads matched the Leishmania genome. In the second patient’s plasma, no Leishmania sequences were detected by mNGS, and the third patient’s plasma was unavailable. All three pathogens were identified as Leishmania infantum. Leishmania amastigotes were observed by microscopic examination of bone marrow smears in all three patients, but were not found in peripheral blood smears. This indicates that the sensitivity of mNGS is higher than that of smear microscopy and that mNGS can be used to identify Leishmania at the species level. Case information indicated that all three patients were elderly male farmers, two from Shanxi and one from Beijing. All three patients had splenomegaly and pancytopenia. Originally, these patients were misdiagnosed and treated for extended periods in other hospitals. Diagnosis of visceral leishmaniasis took place 6 months, 2 months, and 2 months after the onset of symptoms in the three patients, respectively. In conclusion, this study confirms that bone marrow mNGS can be used to quickly and accurately confirm a diagnosis in patients with suspected leishmaniasis.